Electromagnetic wave/particle duality and its applications for Interstellar Propulsion Systems - Goh, Javier Zhin Hsien (2018)
Humanity has made tremendous advancements in technology in the past centuries to go from a land-dwelling species to flight-capable and now, the beginnings of a space-faring civilisation. As humanity further advances into the foreseeable future, we will certainly expand beyond the confines of our own solar system. Interstellar travel has long been the realm of science-fiction and human imagination, yet there have been many concepts proposed to take humanity to the stars, concepts ranging from near-term possibilities to physical impossibilities. Electromagnetic waves are known to exist in its dual nature of wave and particle form, containing energy yet being massless. This characteristics of electromagnetic waves lend itself very favourably to the application of spacecraft propulsion, which is severely limited by the ability to contain as much energy in as little mass as possible. With a massless power source, this could potentially unlock the chains that shackle humanity’s interstellar ambitions. This study aims to characterise and understand the workings of various proposed methods of spacecraft propulsion that rely primarily on electromagnetic waves in some form. It will then compare the systems against a fixed criteria of mission profiles, which are deemed as likely mission profiles for future manned or unmanned exploration or colonisation missions, to the nearest neighbouring star system, the Alpha Centauri system. This study will then conclude with the most ideal propulsion systems for such future missions, as well as a direction towards further research.